Inflation and Monetary Reform - Agenor, Pierre-Richard (IMF Working Papers; Working Paper, 1992)
The introduction of a new currency has often occurred as part of a program to fight hyperinflation. In this context, non-uniform conversion rates for different types of assets and liabilities have been used as a means of reducing an initial 'excess' stock of liquidity. The paper examines the anticipatory dynamics associated with such reforms. The analysis suggests that monetary reforms of this type have a deflationary effect upon announcement as well as during the transition period. Under uncertainty about the reform date, the direction of the initial jump in prices upon announcement is a priori ambiguous. Upon implementation, a monetary reform leads to a downward jump in prices.